Pregnancy and Obesity - Farine, Dan; Maxwell, Cynthia (Hot topics in perinatal medicine., 2017)
Obesity epidemic is a global problem of the 21th century for women in reproductive age and also the obstetricians and pediatricians. There are influences of mother's prepragnancy and antepartal obesity, at delivery, for fetal programming and for maternal.